(untitled) (Geography and Tourism, 2017)
The paper presents an analysis of characteristics of changes in the slope runoff and the maximum water discharge during spring floods in small and medium river basins located in the Ural region. It has been shown that the ongoing degradation of natural catchment systems is manifested not only in the form of a reduced number of species in plant communities and their productivity, but also by transformations in the slope runoff and an increase in the maximum values of slope runoff during spring floods in river basins of different categories. This is evidenced by our longterm observations conducted at nature research stations and during long-term research expeditions. The growing human impact is accompanied by a large number of negative economic and ecological processes occurring in river basins and they should be addressed immediately. These processes are manifested in the form of erosion, riverbed deformations, as well as flooding and destruction of various objects, etc.